The Electrophysiological Features in X-Linked Charcot-Marie-Tooth Disease With Transient Central Nervous System Deficits - Wen, Qingxian; Cao, Longqiao; Yang, Cun; Xie, Yanchen (Frontiers in Neurology, 2018)
Background: Electrophysiological examination plays an important role in the diagnosis of X-linked Charcot-Marie-Tooth disease (CMTX1) with transient central nervous system deficits. However, the electrophysiological features are seldom reported. Methods: We reviewed and analyzed published reports to determine the electrophysiological features of CMTX1 patients with transient central nervous system deficits. Results: A total of 21 CMTX1 patients with transient central nervous system deficits were found in 17 published case reports/series. The age of onset ranged from 0.5 to 18 years (mean 12.02 ± 0.78 years). All patients were male. Recurrent episodes of central nervous system deficits were reported in all 21 cases and resolved in periods ranging from several minutes to 3 days. All 20 patients who had MRIs at presentation had bilaterally symmetrical abnormal T2/Diffusion signals in the white matter without enhancement of gadolinium. All subsequent MRIs showed improvement or were within normal limits. The median motor nerve conduction velocity (MNCV), motor latencies, and compound muscle action potential (CMAP) amplitude were the most commonly measurable electrophysiological parameters (85.7%). All cases that had MNCV at presentation had slower and significantly decreased MNCV compared with the normal value (34.1 ± 1.10 m/s vs. 46.8±2.05 m/s, P < 0.0001; 95% CI, −17.4 to −7.92). The average variations of MNCV in median nerve, ulnar nerve, peroneal nerve, and tibial nerve were 22.0 ± 5.96%, 27.6 ± 11.9%, 25.9 ± 4.36%, and 27.3 ± 4.30%, respectively. All cases with measured sensory nerve conduction velocity (SNCV) at presentation had slower and significantly decreased SNCV compared with the normal value (35.3 ± 1.33 m/s vs. 47.7 ± 2.40 m/s, P < 0.001; 95% CI −18.2 to −6.46). The average variations of SNCV in median nerve, ulnar nerve, and sural nerve were 19.9 ± 8.24%, 25.2 ± 7.75%, and 23.2 ± 3.95%, respectively. Conclusion: This case series serves as a reminder that electrophysiological examination should be included in the diagnosis of recurrent and episodic neurological deficit with white matter lesions. Median MNCV is a sensitive and valuable parameter to support the diagnosis of CMTX1 with transient central nervous system deficits.